‘Whatsapp’ sebagai media pengembangan relasi antarpersonal mahasiswa baru UINSA di masa pandemi - Maulidatus Syahrotin Naqqiyah; Luluk Fikri Zuhriyah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2021)
A pandemic period demands all network-based community activities. Including educational activities ranging from elementary to tertiary level. This has a huge impact on social relations between communities. As a new student at a university, of course, really need a relationship to support the smoothness of the lecture process. This centralized activity in the network greatly hampers the development of relations between students because they are still strangers to one another. This research examines the development of interpersonal relationships during a pandemic. By using the WhatsApp messenger application, new UINSA Surabaya students can easily improve relationships or interpersonal relationships with fellow new students or lecturers, and other academics. This research uses descriptive qualitative research methods. Data collection in this study used in-depth interviews and observations with several informants. This research refers to the social penetration theory of Irwin Altman and Dalmas Taylor. This theory identifies a series of stages in developing a relationship, namely the first stage of orientation, the second stage of exploration-affective, the third stage of affective, the fourth stage is stable, and the last stage is depression. In this study, it was found that in improving interpersonal relations, a concept or a sense of mutual need between communication actors should be created. In addition, an open attitude must also be owned by each individual. And the last is communication ethics that must be owned and applied to create a harmonious relationship.Â